PENINGKATAN HASIL BELAJAR SISWA KELAS XI PADA MATERI KEBENCANAAN DENGAN MODEL PEMBELAJARAN GEOGRAFI BERBASIS SERVICE LEARNING - Malik, Gregorius Agung (Jurnal Geografi, 2023)
This research aims to: (1) improve students' ability to learn and understand the types of institutions that play a role in managing natural disasters; (2) to improve student learning outcomes. This classroom action research was conducted at SMA Negeri 1 TasiFeto Barat class X in the 2019/2020 academic year. The data collection method is by using tests to determine student learning outcomes and observation. The data analysis technique used is descriptive quantitative and qualitative analysis. The results of the research showed that in the first cycle of service learning, the teacher's performance did not provide enough time for students to digest the introductory material, the teacher did not provide enough time for students to master the practice of serving victims of natural disasters in depth. Cycle II, the teacher's performance in achieving the results obtained turned out to be 50.00% which had not been completed in taking the test. Cycle III, the general teacher performance of class Meanwhile, the results of the final test in cycle I, in terms of learning completeness (KKM=76), only 9 students (25.00%) have reached it and 27 students (75.00%) have not yet reached it. This means that the ability of learning outcomes to understand the material of institutions that play a role in managing natural disasters using the service learning model is not yet optimal. Cycle II of the test results found the following results, a student can be said to have good understanding if he has a completeness score of 76 with 80 percent or more. Meanwhile, classical completeness can be said to be successful if 90 percent or more have achieved an individual score of at least 76. So it can be said that the level of understanding of each student is still low because there are only 18 out of 36 people who achieved a score >76, and classical learning completeness is 50% . Cycle III, from the test results, the following results were found, a student can be said to have good understanding if he has a completeness score of 76 with 80 percent or more. Meanwhile, classical completion can be said to be successful if 90 percent or more have achieved an individual score of at least 76. Thus it is concluded that the application of the service learning learning model can improve the learning outcomes of class low.